Moralność finansowa polskich konsumentów - Lewicka-Strzałecka, Anna (Annales. Etyka w Życiu Gospodarczym, 2019)
The consent to abuse made by consumers reflects a particular normative order which constitutes part of a socially accepted moral order. It constitutes a specific market regulator because the wide acceptance of unethical behaviours can hinder the functioning of legal and other formal institutions, while the lack of such acceptance can support them and make them more efficient. The paper presents the results of a periodical research project aimed at reconstructing this order in the financial area. The project, entitled “The Financial Morality of Poles”, includes a survey of a group of 1000 Polish adults from the whole country. The survey has been conducted on a yearly basis since 2016. The main result of the project is a map of Poles’ moral permissivism in the area of finance. The map is based on questions the respondents were asked about the level of justification of consumer activities which are illegal or which violate moral norms. Ethical standards for judging consumers’ behaviours vary considerably, from behaviours that are condemned by the overwhelming majority to behaviours deemed justifiable by more than half of the respondents. It was assumed that, based on the results obtained in individual questions, an estimate of consumer reliability on the financial market can be made. This estimate results from averaging the responses which accept the behaviours described in the questions and is defined as the acceptance index for unethical financial behaviours.